Negotiating sovereignty and human right [ actors and issues in contemporary human rights politics - Cox, Michaelene; Shawki, Noha (Farnham, England;Burlington, Vermont : Ashgate, 2009)
Presenting an overview of institutional developments and innovations in human rights politics, this book discusses some of the most important human rights issues. It focuses on actors and/or issues that are outside the mainstream of international human rights politics
Description based on print version record
Includes index
Includes bibliographical references and index
Keywords: Human rights; Human rights workers; Sovereignty